Comparative Analysis of the Effectiveness of Special Economic Zones and Their Influence on the Development of Territories - Sinenko, Olga; Mayburov, Igor (International Journal of Economics and Financial Issues, 2017)
One of the key issues of the functioning of special economic zones (hereinafter SEZ) is the effect that the tax incentives they offer has on the state and their home areas. The purpose of this article is to perform a comparative analysis of special economic zones of industrial type that won the Global Free Zones of the Year 2015 awards. By summarizing China’s experience of conducting a comprehensive evaluation of SEZs’ effectiveness we were able to identify the main methods that are used for evaluating the effectiveness of SEZs. To perform the analysis, we use financial indicators such as direct investment, revenue shortfalls because of tax incentives, direct financial subsidies as well as indicators that reflect the impact of SEZs on the development of their home territories: people’s income, employment, GDP. The article presents a comparative analysis of the impact of SEZs on the development of their home territories using the case of the leader zones in the following regions: Europe – Alabuga SEZ, Republic of Tatarstan (Russia); Central and Eastern Europe - Katowice Special Economic Zone, Poland, Latin America and Caribbean - Zona Franca Santiago, Dominican Republic. The results of the analysis prove that the SEZs have a positive effect on the development of their home territories, for example, by driving up direct foreign investment and GPD per capita. At the same time, SEZs have no influence on the size of the population and the unemployment rate there. Keywords: special economic zones, tax incentives, the effectiveness of tax incentives. JEL Classifications: O01, H21, H23